Comparative assessment of distance covered, lung function and quality of life after cardiorespiratory rehabilitation with and without transcranial photobiomodulation in individuals with spasticity – Pilot study (Research, Society and Development, 2022)
The aim of the study was to evaluate the effects of cardiorespiratory rehabilitation (CR) alone and associated with transcranial photobiomodulation (PBMt) on distance walked (WD), pulmonary function and quality of life in individuals with spasticity. Participants were divided into two groups: Transcranial photobiomodulation group (PBMtG, CR + active PBMt, n=8) and placebo group (PG, CR + sham PBMt, n=7). The CR consisted of 12 weeks of treatment, 2x week for 1 hour, including aerobic, respiratory and resistance exercises of the lower limbs. For PBMt, the laser cluster was used (λ= 680 nm and 3 lasers at λ= 808 nm, total energy of 36 J/point) at points F7, F8, AFz. WD, spirometry, manovacuometry and SF-36 were evaluated at baseline and reassessment at 8 and 12 weeks. The WD increased by 165.43 meters and 222.46m at 12 weeks for PBMtG and PG, respectively, with intragroup statistical differences (p0.05). An increase in the peak expiratory flow index was observed only in the FG in the baseline analysis x12 weeks (p